Experimental investigation of taper angle during millisecond laser drilling of 18CrNi8 steel under multiple parameters and defocused plane. (8th May 2019) - Nawaz, Saad; Awan, Muhammad Bilal; Saeed, Baber; Abbas, Naseem
Abstract: Laser percussion drilling is widely used for drilling accurate dimensional precise holes. In drilling holes, taper angle has sufficient influence on the shape of the hole. Present experimental analysis is focused on the impact of Nd:YAG millisecond pulsed laser drilling's operating parameters on the entrance and exit hole geometry. Research has provided guidelines to optimize the operating parameters for generating precise hole geometry. Key operating parameters (Laser pulse width/energy, current, number of pulses, gas pressure, beam intensity and frequency) are experimentally investigated for the percussion laser drilling operation. High grade steel (18CrNi8) is selected as workpiece material. 18CrNi8 is one of the preferred material for manufacturing fuel injection nozzles. A novel technique is developed. In this technique, taper angle has been divided into two parts, left taper angle and right taper angle that resulted in better measurement accuracy of the drilled hole. Experimentally obtained results are compared with ideal formulated theoretically calculated values. Due to better technique, drilled hole precision has increased and the difference between ideal and experimental results is less than 5% for all analyzed cases. Results evaluation from straight to blind hole under empirical influence of defocused plane has also been investigated at different levels. This extensive experimentation has led to the conclusive results that will aid in future experimentation and laser drilling processes to obtain optimal hole profile.